Working within/against institutional expectations: Exploring recommendations for social investment in the Oil and Gas sector. Issue 1 (January 2019) - Rabello, Rafaela Costa Camoes; Nairn, Karen; Anderson, Vivienne
Highlights: Oil and Gas social investment experts discussed how to best engage with the community, government and company when developing social investment. Social investment experts adopted working with, working on and working around discourses when discussing their social investment ideals. Participants' accounts of working in the Oil and Gas sector revealed their negotiation of conflicting social investment expectations, which were often at odds with their ideals. Social investment experts play an important and complex role in the Oil and Gas sector, that needs to be understood more fully. Abstract: Globally, Oil and Gas (O&G) companies are increasingly investing in social programmes. The benefits of these programmes for host communities depend on the extent to which programmes are grounded in a community-centred approach to social investment. In this article, we report on a study that explored O&G social investment experts' understandings of and recommendations for social investment in the O&G sector; and how these revealed different approaches to working with local communities. Data were collected through semi-structured and open-ended interviews. We utilised a post-structuralist theoretical framework for analysing the participants' accounts of working in social investment. The experts identified the following practices as important in planning and enacting social investment: (1) engaging with the community, (2) engaging with the government, and (3) engaging with the companies. However, social investment emerged as being a 'shifting' practice that involved experts balancing their own ideals with corporate (profit-making) imperatives. In this article, we argue that, in negotiating conflicting imperatives, O&G social investment experts do important work, which deserves deeper understanding. The article explores the complexities of their work as community 'translators' and advocates when liaising with companies' decision-making personnel and reflects on the impact of this work on the relationships between companies and impacted communities.